Prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae infection in adolescents in Northern Italy: an observational school-based study - Matteelli, Alberto (2016)
University of Brescia. Department of Infectious and Tropical Diseases. Brescia, Italy.